P42 Establishing an indwelling pleural catheter service for ambulatory management of symptomatic malignant pleural effusion. (15th November 2017) - Parsonage, M; Stevenson, NJ; Paxton, CA
Abstract : Introduction and Objectives: We introduced our Indwelling Pleural Catheter (IPC) Service in 2015 to allow ambulatory management of patients with malignant pleural effusions (MPE). Our aim was to review data to establish our patient group, prognostic indicators, rate of autopleurodesis, complications and length of stay (LOS). Methods: Data was collected from Trust electronic records for patients who had IPC placement for MPE June 2015 – July 2017. In addition to patient demographics and outcomes, LENT prognostic score 1 (pleural fluid lactate dehydrogenase, Eastern Cooperative Oncology Group (ECOG) performance status (PS), neutrophil-to-lymphocyte ratio and tumour type), complications and LOS were analysed. Results: 54 patients had IPC placement, 32 (59%) female. Median age was 71 years (24–92). IPC placement by tumour type based on histopathology: mesothelioma 7 (13%), lung 17 (32%), haematological 1 (2%), breast 12 (22%), gynaecological 5 (9%), renal 1 (2%), other tumour types 11 (20%). Median ECOG PS 3. 59% patients died with median survival of 44 days (4–257). Death by tumour type: mesothelioma 6 (19%), lung 11 (34%), haematological 1 (3%), breast 5 (16%), gynaecological 2 (6%), renal 1 (3%), other tumour types 6 (19%). No recorded complications at insertion. Late infection rate 4/54 (7.4%). IPC removal for autopleurodesis 7/54 (13%), with timing of autopleurodesis occurring at 4–8 weeks 1 (14%), 8–12 weeks 3 (43%), ≥12 weeks 3 (43%). Median LOS=1 day. Patients reported a high degree of satisfaction with the service. Conclusions: Our IPC service has helped us offer a patient focused choice through the use of a validated prognostication tool. We have demonstrated that it is safe and effective, and supports admission avoidance. We believe an IPC service promotes cost and clinical effectiveness, through a more modern approach when managing patients with MPE. References: Clive AO, Kahan BC, Hooper CE et-al. Predicting survival in malignant pleural effusion: Development and validation of the LENT prognostic score. Thorax2014. doi:10.1136/thoraxjnl-2014-205285